Forensic Medical and Legal Evaluation of Damages Caused by Cosmetic Applications - Tunç, Mert; Balcı, Yasemin (The Bulletin of Legal Medicine, 2024)
Objective: This study aims to evaluate the forensic dimension of damages arising from cosmetic applications and determine the issues to be considered in this regard. Methods: Forensic cases who applied to our forensic medicine clinic between 2015 and 2022 to obtain a forensic report due to damage arising from cosmetic applications were retrospectively examined. Results: Out of 26 cases, 20 were women and 6 were men. The procedures were performed in beauty centers in 19 cases and hairdressers/ beauty salons in 7 cases. The complained application was laser epilation in 15, hair dyeing in 4, peeling in 2, botox in 1, tattoo removal in 1, hair transplant in 1, eyebrow microblading in 1, and cryolipolysis in 1. Of the cases, 15 complained of burns on their skin, 6 of skin redness, allergic reaction and scarring, and 5 of lack of dyeing, hair loss, sparse hair growth and burning at the base of the hair. Conclusion: When providing forensic expertise in the damage allegations arising from cosmetic procedures, many factors should be taken into consideration in the evaluation, such as whether there is an official license of the performer, whether there is an indication for the procedure, the method’s suitability for the applied area, hygiene conditions of the application environment, the way of the complication management, the patient’s adherence to the medical recommendations after the procedure.